Clinical effect of ePRO-based symptom monitoring and management on improving survival outcomes in patients with advanced cancer: a single-centre, prospective, randomised controlled trial protocol - Yan Wang; Yi He; Zimeng Li; Lili Song; Lili Tang; Ying Pang; Yening Zhang; Zhongge Su (BMJ Open)
Introduction Symptom management is crucial in cancer care, yet patient symptoms are often overlooked in routine care. There is some evidence that electronic symptom monitoring and management can improve patients’ physical function, symptom control, quality of life and survival outcomes. However, the evidence of the impact on survival outcomes in patients with advanced cancer is still limited and debated. This study aims to conduct a prospective randomised controlled trial by a professional symptom management team to monitor and manage symptoms in advanced cancer patients via an electronic information systems for patient-reported outcomes (ePRO) system (WeChat mini-program) and to verify its effectiveness on improving overall survival.Methods and analysis This is a single-centre, prospective, open-labelled, randomised, parallel-controlled clinical trial targeting patients with advanced cancer. We plan to recruit 940 patients using a stratified block randomisation method based on different tumour types. The control group will receive a symptom management self-care manual (both electronic and paper versions). Similarly, the intervention group will receive the same manual and education while also received symptom management by the hospital’s specialised symptom management team through the ePRO system. The primary outcome is comparison of overall survival between groups at the 24-month follow-up. Secondary outcomes will include quality of life, psychological status and incidence of adverse events.Ethics and dissemination The study protocol and related documents received approval from the Ethics Committee of Peking University Cancer Hospital (IRB) in December 2023 (2023YJZ99). Ethical approval will be obtained before implementing any major study revisions in the future. The results of this study will be disseminated through academic seminars, peer-reviewed publications and academic conferences.Trial registration number ChiCTR2400081247.